Sociodemographic characteristics as predictors of knowledge regarding mode of transmission of Lymphatic Filariasis among population of Nepal - Ramesh Adhikari; Devaraj Acharya; Aakriti Wagle (Public Library of Science (PLoS), 2022)
Introduction The majority of the districts of Nepal (63 out of 77) were detected as prevalent of Lymphatic Filariasis (LF), with an average prevalence of 13 percent ranging from less than one to 39 percent in Nepal. Despite people's ignorance about the LF, the government has a target to eliminate LF by 2020. The study aimed to assess the association between sociodemographic characteristics and knowledge of the mode of transmission of LF. Materials and methods The study used a cross-sectional design. Secondary data from Nepal Demographic and Health Survey 2016 were analysed. Altogether, 11040 participants participated in the study. Sociodemographic characteristics were the independent variables, whereas household heads' knowledge of LF transmission was the dependent variable. Descriptive, bivariate, and multivariate analyses were performed to assess the association between sociodemographic characteristics and knowledge of the mode of transmission. Results Findings showed that only 28 percent of household-heads correctly identified the mode of transmission of Lymphatic Filariasis in the study. Household head's age, sex, wealth status, place of residence in terms of areas, geo-belt and province, migration history, and household assets such as bed nets, Radio, TV were significantly associated with the knowledge of the mode of transmission of Lymphatic Filariasis. Variables: wealth status, sex, residence, eco-belts, possessing bed nets, and Radio appeared as significant predictors for knowledge of the mode of transmission of Lymphatic Filariasis. The richest to the poorest people had lower odds ranging from 0.22 to 0.53 for knowing the mode of transmission of Lymphatic Filariasis compared to the richest people (p = 0.001). Conclusion The study identified the population groups with a low level of knowledge of modes of transmission of Lymphatic Filariasis. Thus, it can be inferred from the study that relevant programs need to focus on women, people residing in the mountains and Terai, and those belonging to the middle and poor wealth index. The study also emphasizes that information, education, and communication materials can effectively impart knowledge of Lymphatic Filariasis.